Гомологичность аминокислотных последовательностей супероксид-дисмутаз и белков, кодируемых на митохондриальном геноме - Береговская, Н.Н.; Савич, А.В. (Биополимеры и клетка, 1989)
Оценена степень гомологичности между аминокислотными последовательностями супероксид-дисмутаз (СОД), субъединиц NADH-дегидрогеназ, кодируемых на митохондриальном геноме (ИЛ), и бактериальной Мn-СОД-дегидрогеназы. При сопоставлении в противоположных направлениях карбоксильные участки NADH-дегидрогеназ наиболее гомологичны митохондриальной Mn-СОД. Некоторые выводы подкрепляются сопоставлением нуклеотидных последовательностей. Оцінено ступінь гомологичности між амінокислотними послідовностями супероксид-дисмутаза (СОД), субодиниць NADH-дегідрогеназ, кодованих на мітохондріальному геномі (ІЛ), та бактеріальної Мn-СОД-дегідрогенази. При зіставленні в протилежних напрямках карбоксильні ділянки NADH-дегідрогеназ найбільш гомологични мітохондріальної Mn-СОД. Деякі висновки підкріплюються зіставленням нуклеотиднихпослідовностей. The degrees of homologous character between amino acid sequences of 4 types of superoxide dismutases (Cu/Zn-SOD, Fe-SOD, Mn-SOD bacterial, Mn-SOD mitochondrial) and fragments of the carboxyl ends of NADH dehydTogenases coded for by rnitochondrial genome (iND4) were estimated. The alignement of lamino acid sequences of SOD and NADH-dehydTOgenase was performed in opposite directions. The highest degree of homology was found between ND4 and mitoclhondrial Mn-!SiOD. Degrees of homology between amino acid and nucJeotide sequences for subunits of ND complexe coded for by mitochondrial genome and bacterial ND were calculated. The evolutionary scheme including mitochondrial and bacterial; ND- and bacterial Mn-SOD is given.